(untitled) (Revista Brasileira de Computação Aplicada, 2018)
3D reconstruction methods can be used to obtain digital models by capturing the shape and appearance of real objects. Due to both scientific and technological advances, low-cost 3D reconstruction is now widely used to reconstruct objects of reasonable geometric complexity using cheap acquisition hardware; however, it is unclear whether or not these devices produce suitable results to preserve cultural heritage artifacts. First, this paper goes over the general concept of 3D reconstruction and the main differences between low-cost and general-purpose 3D reconstruction pipelines, these differences are illustrated using a prototypical low-cost pipeline that has been used to reconstruct heritage artifacts. Then, we present the results of a survey conducted in order to investigate how existing low-cost 3D reconstruction approaches attempted to improve the results of their reconstructions, with an emphasis on the realistic rendering techniques they have used. Throughout the survey process, a categorization for low-cost 3D methodologies was proposed based on the scanning apparatus used by the approaches and other similarities between them. Finally, based on the surveyed studies and the results obtained with the prototypical pipeline, we conclude that it is possible to preserve heritage artifacts using low-cost approaches, granted that modern realism techniques are used to improve the appearance of the models.